2019
DOI: 10.46545/aijser.v2i1.26
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Indicators in Precipitation

Abstract: Our  literature  includes   information  and  explanation  for  indicators   in  chemical  reactions and  principle  of  its  using  which  represented  by (types  of indicators ,pH  of  indicators  , instrumental  precipitation,…) , principles of  precipitation  by indicator  , methods of precipitation  by indicator ,types of  indicators   for  precipitation, conditions of precipitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Further evaluation was done by adding indicators to SLS to observe the reaction of milk. Indicator is a halochromic chemical compound added in small amounts to a solution so that the reaction of the solution can be determined visually [36,37]. Therefore, SLS with or without NaOH [38], and Badiuzzaman et al [25] also reported the lower Se of WST and SFMT.…”
Section: Discussionmentioning
confidence: 99%
“…Further evaluation was done by adding indicators to SLS to observe the reaction of milk. Indicator is a halochromic chemical compound added in small amounts to a solution so that the reaction of the solution can be determined visually [36,37]. Therefore, SLS with or without NaOH [38], and Badiuzzaman et al [25] also reported the lower Se of WST and SFMT.…”
Section: Discussionmentioning
confidence: 99%
“…The redox indicators cause significant electrical or color changes, due to the conversion of the reduced form to the oxidized one [ 170 ]. These indicators must be able to generate a rapid and reversible response, establishing a rapid chemical equilibrium between the reduced and oxidized forms [ 171 ].…”
Section: Classification Of Bio-ppoct Based On Detection Elementsmentioning
confidence: 99%